Structural failure performance of the confined liner with a non-uniformly annular gap subjected to a point load under a thermal rise field. (November 2019) - Li, Zhaochao; Huang, Hao
Abstract: The present investigation focuses on the failure performance of the confined liner with a non-uniform annular gap. The liner is subjected to a radial point load under a temperature rise field. An admissible displacement function is assumed to establish the nonlinear equilibrium equations. The principle of minimum potential energy is employed to obtain the analytical expressions of the critical buckling load (failure load) for the elastic liner encased in the rigid medium. It is found that the temperature rise field has a substantial increase in the critical buckling load. Subsequently, the buckling and post-buckling load-displacement equilibrium paths are plotted by the analytical solutions, and such equilibrium paths can also be traced by developing a two-dimensional (2D) finite element model (FEM). The maximum load (buckling load) obtained from the numerical results show excellent agreement with that from the proposed analytical solutions, and other closed-form expressions. Furthermore, the liners with inelastic material properties and geometric nonlinearities are considered numerically, and the critical buckling load shows its sensitivity to the initial gap, the initial out-of-roundness imperfection, and Young's modulus of the medium. Finally, the effect of friction is examined and plays a small role in the critical buckling load. Highlights: The buckling load of the confined liner under thermal field is derived analytically. The analytical solution is verified successfully by developing a numerical model. The thermal field has a significant effect on the critical buckling load. The effects of the inelastic properties on the stability mechanism are considered.